Putusan Badan Penyelesaian Sengketa Konsumen : Bersifat Final dan Mengikat? - Made Cherina Apriliasari Mantrawan; I Gede Agus Kurniawan (University of Udayana, 2024)
The objective of this scholarly publication is to investigate and assess the Consumer Dispute Settlement Body's (BPSK) authority and the conclusive and legally binding nature of its decisions. This investigation employs normative legal research. The authority and responsibilities of the Consumer Dispute Resolution Agency (BPSK) are specified in Article 52 UUPK. The consumer dispute resolution body is obligated to render a final and binding decision within twenty-one (21) business days from the date of receipt of the lawsuit. This adheres to the provisions outlined in Article 54 paragraph 3 UUPK and Article 55. The ultimate and enforceable interpretation of a Consumer Dispute Settlement Agency decision is fundamentally distinct from that of a court institution's decision bearing the same meaning. This shows that the status and position of the Consumer Dispute Resolution Agency (BPSK) is assessed from an administrative perspective, it only has administrative authority. Therefore, it was deemed that the decision could not have judicial attributes. Consequently, BPSK may be categorized as a quasi-judicial institution, deviating in character from the principal court institutions in terms of the substance of its rulings. Therefore, in light of the BPSK decision's